The effect of oil price fluctuation on the economy: What can we learn from alternative models? - Gil Kim; David Vera (Journal of Applied Economics, 2022)
Following the exisiting literature, we present the most up-to-date estimates of oil shocks and the response of the U.S. economy. Regardless of model specifications, oil supply shocks have a negative effect on the U.S. real GDP, albeit the magnitude of responses is different across models. Aggregate demand shocks and oil-market specific shocks appear to have a positive effect on CPI, while there is little evidence of inflationary impact from the oil supply shocks. Overall, our results suggest that to evaluate the impact of an unexpected change on the price of oil on economic activity, identifying the source of the price of oil fluctuation might be one of the critical steps since the response of the GDP and CPI could vary depending on the source of the shocks.
Keywords: 330; business fluctuations; oil prices; Oil shocks